The Influence of the Two Stay Two Stray Type Cooperative Learning Model on Students' Mathematics Learning Outcomes in Class VII of State Junior High School 1 Batangtoru, Indonesia - Sihombing, Amelia Syakinah (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This research is motivated by the low mathematics learning outcomes of students in class VII of SMP Negeri 1 Batangtoru. One possible cause of the low student learning outcomes is the inappropriate learning model used by teachers in class so that students become passive in the learning process. The purpose of this study was to determine and analyze the effect of the Two Stay Two Stray cooperative learning model on the mathematics learning outcomes of class VII students of SMP Negeri 1 Batangtoru. This research is a quantitative study. The study involved two classes: the control class and the experimental class. The research instrument used a test. Data processing and analysis were conducted using the t-test. Based on the data analysis, the post-test questions given to students to measure students' cognitive abilities obtained an average value of 80.78 for the experimental class and 70.78 for the control class. The results of the hypothesis testing indicate that the t-count is greater than the t-table, specifically 2.941 > 2.0369, with a significance level of 5%. So, the original idea was not supported, and instead, it was found that the two-stay, two-stray cooperative learning model significantly improved the math learning results for seventh-grade students at SMP Negeri 1 Batangtoru, Indonesia.